Synthesis and Evaluation of Radiopharmaceuticals for Imaging Bacterial Infection - Beiraghi, Omid (My University, 2016)
Despite recent advances, radiopharmaceuticals to detect and characterize bacterial infections have a number of limitations. Many of the clinically approved radiopharmaceutical agents are not specific to bacterial infections and accumulate at lesions of inflammation. Hence, new approaches are necessary to detect bacteria with high specificity and selectivity. A library of desferrioxamine B (DFO) derivatives were prepared to create radiolabeled siderophores to create a bacteria-specific imaging probe by exploiting the mechanism bacteria use to scavenge iron, which plays a key role in bacterial growth and biofilm formation Compounds were synthesized using two convenient carbamate forming strategies in 30% to 92% yield. The cold and radioactive gallium (67Ga) complexes were prepared and characterized and their uptake by S. aureus bacteria were assessed in vitro and in vivo. In vivo studies revealed that 67GaDFOethoxycarbamate had uptake comparable to GaDFO that was blockable, showing the compound was actively taken up via the siderophore pathway. In vivo studies in a mouse model resulted in a good infected to non-infected thigh ratio (11:1) and non-specific uptake by the GI tract. Bioorthogonal chemistry was also explored as an approach for imaging infection using trans-cyclooctene (TCO) functionalized vancomycin and a tetrazine functionalized 67GaDFO (67GaDFO-Tz) complex.2,3 In vitro results revealed that allowing vancomycin-TCO to bind S. aureus prior to the addition of 67GaDFO-Tz (pretargeting) showed higher (63%) uptake than with a conjugate formed prior to incubation with the bacteria (direct targeting, 28%). For the bioorthogonal approach, the distribution of the 67GaDFO-Tz was assessed in a S. aureus infection murine model, which showed significant uptake of 67GaDFO-Tz in the GI tract 1 h post intravenous injection. However, uptake in the infected joint was evident at 71 h post infection. The data suggests targeting bacteria using TCO-labeled antibiotics and radiolabeled tetrazines is a feasible strategy, but that further optimization of the vancomycin injection dose and injection time are necessary.
Keywords: bacterial infection; imaging; SPECT; gallium-67; siderophores; deferoxamine; antibiotic; vancomycin